2019
DOI: 10.3390/cells8080837
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Role of l-Dopa Decarboxylase in Flaviviridae Virus Infections

Abstract: l-dopa decarboxylase (DDC) that catalyzes the biosynthesis of bioactive amines, such as dopamine and serotonin, is expressed in the nervous system and peripheral tissues, including the liver, where its physiological role remains unknown. Recently, we reported a physical and functional interaction of DDC with the major signaling regulator phosphoinosite-3-kinase (PI3K). Here, we provide compelling evidence for the involvement of DDC in viral infections. Studying dengue (DENV) and hepatitis C (HCV) virus infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
50
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(68 citation statements)
references
References 102 publications
13
50
2
Order By: Relevance
“…The antiviral screening performed by combined strategy showed that, in the DENV-2 model, all compounds increased the production of infectious viral particles ( Figure 2 A). This, seemingly pro-viral, type of response has been previously reported in this model for α-tocopherol, melatonin [ 29 ], and carbidopa [ 25 ]. This last compound inhibits the enzyme L-dopa decarboxylase (DDC), which negatively regulates flavivirus replication, leading to an increase in viral replication [ 25 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The antiviral screening performed by combined strategy showed that, in the DENV-2 model, all compounds increased the production of infectious viral particles ( Figure 2 A). This, seemingly pro-viral, type of response has been previously reported in this model for α-tocopherol, melatonin [ 29 ], and carbidopa [ 25 ]. This last compound inhibits the enzyme L-dopa decarboxylase (DDC), which negatively regulates flavivirus replication, leading to an increase in viral replication [ 25 ].…”
Section: Discussionsupporting
confidence: 74%
“…The limited natural sources of this type of compounds led to the use of isolated bromotyrosines structures as pharmacophores and allow the de-novo synthesis of new dihalogenated compounds derived from L-tyrosine that contain different structurally associated substitutions that already demonstrate biological and anti-parasitic activity [ 23 ]. Additionally, other tyrosine derivatives such as L-Dopa have previously demonstrated their antiarboviral activity and modulate signaling pathways related to viral replication [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 The potential protective role of dopamine in the context of viral infections has been poorly investigated until now. In this regard, it is worth noting that in a recent work, DDC was found to negatively regulate the replication of the Flaviviridae viruses dengue and hepatitis C. 10 Experimental research works are needed to clarify the links between ACE2 and DDC during SARS-CoV2 infection. Moreover, in patients suffering from severe forms of COVID-19, the hypothesis of a systemic failure of the dopamine synthetic pathway should be taken into account and further explored.…”
mentioning
confidence: 99%
“…In the pathway enrichment analysis, many up and down-regulated genes may play a very key role in the progression of SARS-CoV-2 infection. Enriched genes such as CXCL9 [58], CX3CL1 [59], IFNB1 [60], IL7 [61], TNFSF10 [62], IFNL3 [63], EGR1 [64], USP18 [65], DDX58 [66], UBA7 [67], IFI35 [68], IFIT2 [69], IFIT1 [70], TRIM5 [71], RSAD2 [72], XAF1 [73], MX2 [74], GBP1 [75], TRIM21 [76], FGF19 [77], PELI1 [78], OAS1 [79], DUSP10 [80], TLR6 [81], TICAM1 [82], DDC (dopa decarboxylase) [83], UGT1A1 [84], STMN1 [85], CYP27A1 [86] and ACE (angiotensin I converting enzyme) [87] were linked with advancement of various viral infections, but these genes may be responsible for progression of SARS-CoV-2 infection as well. Enriched genes such as CCL2 [88], FLT3 [89], CXCL8 [90], IL11 [91], CXCL10 [92], TNF (tumor necrosis factor) [93], EGR2 [94], TRIM22 [95], PML (promyelocyticleukemia) [96], ICAM1 [97], IFITM1 [98], IFITM2 [99], ISG15 [100], SOCS1…”
mentioning
confidence: 99%